Relationship Between the Orthorhombic and Hexagonal Phases in Dy2TiO5. Issue 11 (30th June 2016) - Seymour, Kevin C.; Ribero, Daniel; McCormack, Scott J.; Kriven, Waltraud M.
Abstract : The thermal expansion of Dy2 TiO5 in the hexagonal phase was evaluated and compared with the orthorhombic phase using in situ high‐temperature X‐ray diffraction. The crystal structure, volume changes before and after the transformation process, as well as the mechanism behind the thermal expansion behavior was determined and proposed. It was found that in the hexagonal phase, the thermal expansion was caused by the oxygen anions in the axial positions of the trigonal bipyramidal structure moving toward the central Ti atom. While expanding, the movement of these oxygen anions slows the expansion along the c ‐axis resulting in a decrease in α33 with temperature. Furthermore, a structural relationship between the orthorhombic and the hexagonal phases was proposed.